TAXATION OF DIGITAL ECONOMY IN INDIA: ISSUES AND POLICY RECOMMENDATIONS (International Journal of Food and Nutritional Sciences, 2021)
The taxation of the digital economy in India presents multifaceted challenges rootedin the globalized and intangible nature of digital transactions. The primary challenge lies indetermining taxable presence or Permanent Establishment (PE) of digital companiesoperating remotely in India. Current PE rules, designed for physical presence, often fail tocapture significant economic activities conducted digitally. This complicates profitattribution, as digital business models heavily rely on intangible assets like algorithms anduser data, making it difficult to allocate profits across jurisdictions accurately. Furthermore,aggressive tax planning strategies, such as transfer pricing and IP shifting to low-taxjurisdictions, contribute to base erosion and profit shifting (BEPS), undermining India's taxbase. Data localization requirements further complicate tax implications by mandating localstorage of user data, influencing how digital companies structure operations and comply withtax laws. India's introduction of an Equalization Levy (EL) on specified digital services aimsto address these challenges but has raised concerns regarding compliance costs andinternational tax norms alignment. To navigate these challenges effectively, India shouldupdate its tax rules to include digital-specific provisions, such as significant economicpresence (SEP) criteria aligned with global standards. Multilateral cooperation throughforums like the OECD can harmonize digital taxation rules globally, reducing tax disputesand enhancing compliance. Leveraging data analytics and digital tools can improve taxadministration capabilities, enabling better monitoring of digital transactions andenforcement of tax laws. Simplifying compliance procedures and providing clear guidelinescan mitigate ambiguity and reduce compliance costs for digital firms. Additionally, fosteringan environment that supports digital innovation through targeted tax incentives and R&Dcredits can stimulate economic growth while ensuring fair taxation.